Measurement of Aspirin Concentrations in Portal and Systemic Blood in Pigs: Effect on Platelet Aggregation, Thromboxane and Prostacyclin Production - Bochner, F; Siebert, D M; Rodgers, S E; McIntosh, G H; James, M J; Lloyd, J V (Thrombosis and Haemostasis, 1989)
Low doses of enteric-coated aspirin were administered orally to pigs. Plasma aspirin concentrations measured in blood obtained simultaneously from permanent catheters in a systemic artery and portal vein for 6 hours after dosage showed a large variation in the plasma aspirin concentration : time profile between pigs. After 50 mg single dose the ratio of the arterial : portal area under the plasma concentration versus time curve (AUC) was 0.63 ± 0.08 (mean ± SE, n = 6). In three pigs which received all three dosage regimens, the arterial : portal AUC ratios were 0.48 ± 0.05 after 50 mg single dose, 0.52 ± 0.02 after 100 mg single dose and 0.47 ± 0.02 after 100 mg daily for 1 week. Platelet aggregation in response to sodium arachidonate (1.65 mM) was completely abolished after chronic aspirin administration of 100 mg daily. Thromboxane production (pg/ 106 platelets) induced by this stimulus decreased from 536 ± 117 before aspirin to 57 ± 14 after aspirin (mean ± SE, n = 4; p = 0.03). Aortic prostacyclin synthesis, measured as 6-keto PGF1α (ng/disc after 10 min incubation), was 1.66 ± 0.28 (mean ± SE, n = 4) in untreated pigs and 0.95 ± 0.25 (n = 5) in treated pigs (p = 0.07). Results from this study support the idea that a difference between aspirin concentrations in the portal and systemic circulations can be achieved. Whether this can be translated into a clinically useful differential effect on the vessel wall compared to the platelet remains to be determined.
Keywords: Aspirin; Hepatic metabolism; Prostacyclin; Thromboxane